The Synergy of Nanosilica and Zinc Diethyl Hypophosphite Influences the Flame Retardancy and Foaming Performance of Poly(Ethylene Terephthalate) - Jiaxin Zheng; Congxiao Wang; Yuyin Zhao; Menghao Guo; Yadong He; Chunling Xin (Advances in Polymer Technology)
In order to improve the flame retardancy of poly(ethylene terephthalate) (PET) and maintain its excellent foamability, nanosilica (nano-SiO2), and zinc diethyl hypophosphite (ZDP) were selected as synergistic flame retardants, and pyromellitic dianhydride (PMDA) was used as a chain extender to carry out flame retardant and chain extension modification of PET simultaneously. The flame retardancy and flame-retardant mechanism of modified PET were characterized by limiting oxygen index, vertical combustion test, thermogravimetric analysis, and SEM. Dynamic rheological test and DSC were used to analyze the rheological and thermal properties. The foaming ability was also studied by batch foaming experiments. The test results indicated that nano-SiO2 and ZDP had a synergistic effect, which could significantly improve flame retardancy of PET. The vertical combustible grade of modified PET reached V-0 grade, and the limiting oxygen index increased from 21% to about 30%. The role of nano-SiO2 on the flame retardancy of PET was mainly to increase compactness and strength of the carbon layer, which could block combustible gas produced by the pyrolysis of PET and resist dripping behavior. At the same time, the addition of nano-SiO2 increased the crystallization temperature and crystallinity of PET. Otherwise, nano-SiO2 could act as a bubble-nucleating agent and improve the foaming ability of modified PET. When the addition amount was 1 wt%, not only did the maximum foaming ratio increase but the foaming temperature zone was also widened from 225°C-235°C to 225°C-250°C. Finally, a flame-retardant PET system with good foaming property was proposed.